(untitled) (Research, Society and Development, 2021)
Nutrigenomics studies have identified genetic variants that influence specific nutrient intake and metabolism and predict the variability of individuals in response to dietary interventions. Metabolomics revealed the metabolic impressions of food and nutrient consumption and discovered new metabolic pathways potentially modified by diet. This work aimed to investigate the scientific evidence that proves the effectiveness of nutrigenomics in food and the prevention of chronic non-communicable diseases, as well as the impact of nutrients in the modulation of gene expression and prevention of these pathologies. It is an integrative review that allows combining data from the theoretical literature that can guide the definition of concepts, identification, review and methodological analysis of studies on the subject. Evidence from gene-nutrient interaction studies with CNCDs is relevant not only for identifying the influence of a particular gene on a phenotype in a population with different dietary habits that can potentially affect this phenotype, but also for evaluating the response of a dietary intervention among individuals with different genotypes. The study related to nutrigenomics, more specifically with nutritional genomics, brings several relevant and very important aspects, possible benefits for improving the quality of life, making it possible to modulate gene expression in the human genome through bioactive compounds and nutrients in food.